Time period effects in work disability due to common mental disorders among young employees: Muhammad Ridwanul Amin. (25th October 2022) - Amin, M; Mittendorfer-Rutz, E; Björkenstam, E; Virtanen, M; Helgesson, M; Gustafsson, N; Rahman, S
Abstract: Background: Previous research on period effects in risk for work disability due to common mental disorders across employment sectors and occupational classes in young employees is lacking. Temporal changes in the healthcare system or social insurance policies or other structural/organisational changes could contribute to such time period effects. We aimed to investigate time period effects in the risk of work disability, defined as long-term sickness absence (LTSA) and disability pension (DP) due to common mental disorders (CMDs), among young employees according to their employment sector (private/public) and occupational class (non-manual/manual). Methods: Three cohorts, including all employed individuals with complete information on employment sector and occupational class, aged 19-29 years and resident in Sweden on the 31-Dec-2004, 2009 and 2014 (n = 573, 516, 665, 138 and 600, 889 individuals in cohort 2004, 2009 and 2014, respectively) were followed for four years. Crude and multivariate-adjusted hazard ratios (HRs and aHRs, respectively) with 95% confidence intervals (CIs) were estimated regarding the risk of LTSA and DP due to CMDs using Cox regression analyses. Results: In cohort 2004, public sector employees had a higher relative risk for LTSA due to CMDs than private sector employees (aHR, (95%CI): 1.24, 1.16-1.34 and 1.18, 1.11-1.26 among non-manual and manual workers). These associations were similar in the later cohorts. Compared to cohort 2004, the rate of DP due to CMDs was considerably lower in the later cohorts leading to uncertainties in the risk estimates limiting the comparability for time period effects regarding the risk of DP due to CMDs across employment sectors and occupational classes. Conclusions: Stricter regulation changes regarding the receipt of DP in Sweden, rather than other time period events, may have differentially affected the risk of work disability among young non-manual and manual employees working in the private and public sectors. Key messages: Time period effects did not seem to influence the association of long-term sickness absence due to common mental disorders across employment sectors and occupational classes. The risk of disability pension due to common mental disorders by sector of employment and occupational class varied, to some extent, across the different time period cohorts.